KEDUDUKAN ANAK LAKI-LAKI DALAM SISTEM PEWARISAN PADA PERKAWINAN ETINIS TIONGHOA BERDASARKAN KEADILAN - Anandadhea Putricharina; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Inheritance law is a body of regulations that governs the wealth left by the heir andthe effects of this transfer on those who inherit it, both in terms of their relationships with oneanother and with other people. All rights and duties are instantly transmitted to the heirsupon death. According to teachings, the Chinese ethnic community frequently appliescustomary law. The position of a tall boy is more assured. It has long been accepted amongthe indigenous Chinese population that only sons are entitled to the whole inheritance, whilefemales can only inherit jewels. In according to Article 131 IS, which applies to the CivilCode, the Chinese community is considered a population group for the purposes ofinheritance distribution. The goal of this thesis is to investigate the status of sons in thesystem of son inheritance in ethnic Chinese marriages and to learn about the system of soninheritance in ethnic Chinese marriages based of justice.This type of research is empirical research. Basically, it is a comparative studybetween legal ideals and legal reality in the form of actions (law in action). The data sourcesused consist of primary legal materials, secondary legal materials and tertiary legalmaterials. Data collection techniques in this study were carried out by interviews andliterature studies by taking quotations from the literature that had links with the problems ofthis research.The results of the research conducted, there are several conclusions obtained,namely: First, Chinese customs do not regulate in writing regarding the position of children,in practice the position of sons in ethnic Chinese is higher than that of women which iscarried out from generation to generation. Second, justice can be guaranteed from thebinding nature of codified civil regulations in the process of resolving cases of inheritancedistribution in ethnic Chinese communities.Keywords: Inheritance System – Chinese – Boy Position.